Eurorégiók szerepe a határ menti turisztikai együttműködésben - Remenyik, Bulcsú; Bujdosó, Zoltán (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The Euroregion indicates such geographical areas, which include the areas of two or more countries. They agreed in the fact, that they coordinate their activities in the interest of the development of the borderlands (Siili-Zakar 1998). So this is an area in which different kinds of coorporations exist between two or more states and local governments. Theses are mainly interregional, transnational, economical, social or cultural coorporations (Éger 2000). The most important tasks of the Euroregion are to help the coordination between the borde areas, to support enterprises, to reduce migrational limits and to organize transport connections. Apart from these, a number of social, economical (e.g. police or criminal coorporation) activities can happen between borders (Mátyás 2008). Compared to our region, the length of our borders is large and the main part of our inhabitants live in frontier areas, since fourteen of our counties border with the neighbouring countries (Rechnitzer 1999).